PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN MELALUI PERILAKU PRODUKTIF PADA PT. SARI DUMAI SEJATI - Tarigan , Lilis Handayani; Indarti , Sri; Pailis, Eka Armas (Komunitas Manajemen Kompetitif, 2025)
This research aims to see and determine the direct and indirect influenceregarding the Effect of Implementing Total Quality Management and EmployeeEngagement on Employee Performance through Productive Employee Behavior.The population in this research is all employees of PT. Sari Dumai Sejati, totaling138 people, using SEM. In this research, the sampling method uses the CensusTechnique, namely a sampling technique in which the entire population is selectedas sample members so that the sample becomes 138 respondents. Total QualityManagement and Employee Engagement have a significant effect on productivebehavior. Total Quality Management, Employee Engagement and productivebehavior have a significant effect on employee performance. Productive behaviorhas a significant effect on employee performance. And productive behavior is ableto mediate Total Quality Management and Employee Engagement with a significanteffect on employee performance